Northern Love: An exploration of Canadian Masculinity - Paul Nonnekes (Cultural Dialectics, 2008)
In Northern Love, Paul Nonnekes pursues debates in psychoanalysis and cultural theory in pursuit of a distinctive conception of a Canadian masculinity. In close discussions of novels by Rudy Wiebe ( A Discovery of Strangers ) and Robert Kroetsch ( The Man from the Creeks ), Nonnekes ranges from Hegel to Lacan, and Butler and Kristeva to Žižek, eliciting an evolving conception of love characteristic of the Canadian cultural imaginary. It is the first book in the Cultural Dialectics series, edited by Raphael Foshay of Athabasca University.